ANALISIS PENGARUH KESEMPATAN INVESTASI, INTERNAL CASH FLOW, INSIDER OWNERSHIP TERHADAP CAPITAL EXPENDITURE: PERSPECTIVE PECKING ORDER THEORY - YEANNIE YEANNIE; RATIH HANDAYANI (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2007)
The objectives of this study were to observe the effects of investment opport-tunity, internal cash flow and insider ownership on the capital expenditures in one of the pecking order theory perspective. The pecking order hypothesis postulates that financing for the capital expenditures would take from the internal cash flow first, meant of more higher the financing take from the internal cash flow which impact with the amount of capital expenditures. Managers can choose the level of capital expenditures to maximize the wealth of current shareholders without considering insider ownership in the company. The Population of this study were 138 companies that listed in Jakarta Stock Exchange with sample were 90 companies which have insider owner-ship inside during 2001 until 2003 that were taken using the purposive sampling method. Data were analyzed using multiple regression analysis. The result of this study shows that the investment opportunity have negative and significant impact on the capital expenditures, and the internal cash flow have positive and significant impact on the capital expenditures. How ever, the impact of insider ownership on the capital expenditures was not significant.